The short story of film : a pocket guide to key genres, films, movements & techniques - Smith, Ian Haydn (Londer: Laurence King Publishing, 2020)
The Short Story of Film is a new and innovative introduction to the art of film-making. Simply constructed, the book explores 50 key movies, from superhero blockbusters to indie darlings. The design of the book allows the reader to navigate their way around key genres, movements and techniques with ease. Accessible, concise and fun to read, this pocket guide will give moviegoers a new way to enjoy their favourite films and to discover new ones to watch.
Machine generated contents note: GENRES -- Western -- Historical Epic -- Race Film -- War -- Action -- Anti-War -- Gangster -- Horror -- Musical -- Romantic Comedy -- Screwball Comedy -- Melodrama -- Propaganda -- Documentary -- Film Noir -- Teen Drama -- Jidaigeki -- Spaghetti Western -- Period Drama -- Art Film -- Slasher -- Giallo -- Conspiracy Thriller -- Police Procedural -- Feminist Film -- Blaxploitation -- Disaster Movie -- Road Movie -- Martial Arts -- Blockbuster -- Sci-Fi -- Psychological Thriller -- Mockumentary -- Hood Film -- Slow Cinema -- Superhero Movie -- KEY FILMS -- Intolerance / D.W. Griffith -- Battleship Potemkin / Sergei Eisenstein -- The General / Buster Keaton -- Sunrise: A Song of Two Humans / F.W. Murnau -- Metropolis / Fritz Lang -- City Lights / Charles Chaplin -- L'Atalante / Jean Vigo -- Bringing Up Baby / Howard Hawks -- The Rules of the Game / Jean Renoir -- Citizen Kane / Orson Welles -- Rome, Open City / Roberto Rossellini -- Singin in the Rain / Gene Kelly -- Tokyo Story / Yasujiro Ozu -- Seven Samurai / Akira Kurosawa -- Rather Panchali / Satyajit Ray -- The Searchers / John Ford -- Vertigo / Alfred Hitchcock -- Some Like It Hot / Billy Wilder -- A Bout de Souffle / Jean-Luc Godard -- La Dolce Vita / Federico Fellini -- L'Avventura / Michelangelo Antonioni -- The Exterminating Angel / Luis Bunuel -- Cleo from 5 to 7 / Agnes Varda -- The Battle of Algiers / Gillo Pontecorvo -- Persona / Ingmar Bergman -- Au Hasard Balthazar / Robert Bresson -- Once Upon a Time in the West / Sergio Leone -- 2001: A Space Odyssey / Stanley Kubrick -- The Conformist / Bernardo Bertolucci -- Aguirre, The Wrath of God / Werner Herzog -- Ali: Fear Eats the Soul / Rainer Werner Fassbinder -- Jaws / Steven Spielberg -- Jeanne Dielman, 23 Quai du Commerce, 1080 Bruxelles / Chantal Akerman -- Taxi Driver / Martin Scorsese -- Apocalypse Now / Francis Ford Coppola -- Stalker / Andrei Tarkovsky -- Blade Runner / Ridley Scott -- Blue Velvet / David Lynch -- Do the Right Thing / Spike Lee -- Close-Up / Abbas Kiarostami -- The Piano / Jane Campion -- Pulp Fiction / Quentin Tarantino -- All About My Mother / Pedro Almodovar -- Beau Travail / Claire Denis -- In the Mood for Love / Wong Kar-wai -- Lost in Translation / Sofia Coppola -- Moolaade / Ousmane Sembene -- There Will Be Blood / Paul Thomas Anderson -- Moonlight / Barry Jenkins -- Roma / Alfonso Cuaron -- MOVEMENTS -- German Expressionism -- Soviet Montage -- Surrealist Cinema -- Poetic Realism -- Italian Neorealism -- Parallel Cinema -- Polish Film School -- French New Wave -- British New Wave -- Japanese New Wave -- Cinema Novo -- Czech New Wave -- New German Cinema -- New Hollywood -- Iranian New Wave -- Australian New Wave -- Hong Kong New Wave -- Cinema du Look -- Taiwanese New Wave -- Chinese Fifth Generation -- New Queer Cinema -- Dogme 95 -- New Mexican Cinema -- New French Extremity -- Mumblecore -- Romanian New Wave -- TECHNIQUES -- Film -- Colour -- Master Shot -- Continuity Editing -- Tracking Shot -- Panning Shot -- Zoom -- Cross-Cutting -- Montage -- Close-Up -- Deep Focus -- Jump Cut -- Film Transition -- Lighting -- Production Design -- Costume Design -- Make-Up -- Star System -- Sound -- Music -- Method Acting -- Cinema Verite -- Slow Motion -- Steadicam -- Special Effects -- Visual Effects -- Digital -- 3D.
Includes index.
Keywords: Motion pictures -- History; Motion pictures; Motion pictures; Filmgeschichtsschreibung; Film; Artet boterore-Arti skenik-Filmi -Kinemaja-Artiste boterore-Aktoret e huaj-Regjizoret e huaj-Teknikat-Zhanret-Historia-Udhezues-Filmat e famshem boterore-; History